A prospective randomized comparative study of umbilical port site complications following fascial sheath closure versus non-closure in laparoscopic surgeries at a tertiary care centre in central India - Gupta, Shweta B.; Mitra, Arti; Gupta, Brajesh B.; Nighot, Gaurav (International Surgery Journal, 2025)
Background: The increase in laparoscopic surgeries has been accompanied by concerns over trocar site complications, particularly port site hernia (PSH). Among surgical debates, the necessity of fascial sheath closure for umbilical ports ≥10 mm remains unresolved. Objective of the study was to compare the incidence of umbilical port site complications between fascial sheath closure and non-closure in laparoscopic surgeries. Methods: A prospective, interventional, randomized study was carried out at a tertiary care centre in Central India from July 2020 to December 2022. 100 patients undergoing elective laparoscopic procedures were enrolled and divided into two groups: group A (fascial closure) and group B (non-closure). Patients were assessed for port site hernia, hematoma, and infection through clinical and ultrasonographic evaluation over a mean follow-up period of 14 months. Results: Port site hernia was observed in 3 patients (3%) overall: 1 patient in the closure group and 2 in the non-closure group (p=1.0). Port site infection occurred in 10 patients: 6 in the closure group (12%) and 4 in the non-closure group (8%) (p=0.688). A single case of port site hematoma was recorded in the non-closure group. No statistically significant differences were observed in hospital stay or complication rates. Conclusion: There is no statistically significant difference in the incidence of port site complications between fascial closure and non-closure groups. Routine fascial closure of the umbilical port may not be essential in all cases.